Analisis Data Pola Pembelian Konsumen Dengan Algoritma Apriori Pada Transaksi Penjualan Minimarket D Mart - Utnasari, Intan (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
Minimarket D Mart is one of the stores that sells various items of daily necessities. Minimarket D Mart when doing a transaction had using a computer but the data only has function as an archive, so that the data piles up. The data stack can obtain new information if it processed property, such as seeing the pattern of what items are of ten purchased by consumers. The study alms to determine the process of data mining analysis with apriori algorithms and to determine the rule which generated from the highest support value and confidence the method used in this study is data mining method with apriori algorithms, apriori included in the group of association rules in data mining. Besides apriori, market basket analysis method also included in its group. Market basket analysis in methodology for analysing consumer buying patterns of finding association between different items. Based in the result, the application of apriori algorithms on data mining technique is very efficient and also accelerate the process of forming trends in combination patterns of sales out come with the highest support value and confidence belong to teh pucuk, aqua with support 54% and confidence 100%.